"The map is not the territory": a boundary objects perspective on supply chain mapping. Issue 9 (7th July 2020) - Fabbe-Costes, Nathalie; Lechaptois, Lucie; Spring, Martin
Abstract : Purpose: To empirically examine the usefulness and value of supply chain mapping (SC mapping), which has been neglected despite its importance in research and practice. Design/methodology/approach: Based on three combined theoretical perspectives, we conducted a case study on a car manufacturer's managers mapping their downstream supply chain (SC). We conducted semi-structured interviews and a mapping exercise with them, followed by a focus group. Findings: We find differences between individual and corporate SC maps and between how managers define the outbound SC, the SC map they draw and what they say when mapping. The three theoretical perspectives allow us to enrich SC mapping thinking. We focus on boundary objects to formulate propositions. SC mapping and maps are discussed with respect to contemporary SCs and SCM. Research limitations/implications: Based on a single case study on one firm's outbound SC. Research could be expanded to the company's external partners and follow the development and use of maps in real time. Practical implications: Highlights the usefulness and difficulties of SC mapping, for individuals and organisations. For the company, it opens avenues for further development and use of SC mapping to improve inter-functional and inter-organisational collaboration. Social implications: Confirms the need for SC mapping competences in SCM and consequently the usefulness of teaching SC mapping courses in logistics and SCM programs. Originality/value: Highlights the usefulness of SC mapping and rekindles interest in SC mapping and maps in SCM. Introduces boundary objects into SCM research.